2010
DOI: 10.1074/mcp.m900396-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium bovis Bacille Calmette-Guérin Phagosome Proteome

Abstract: Mycobacterium tuberculosis and Mycobacterium bovis bacille Calmette-Gué rin (BCG) alter the maturation of their phagosomes and reside within a compartment that resists acidification and fusion with lysosomes. To define the molecular composition of this compartment, we developed a novel method for obtaining highly purified phagosomes from BCG-infected human macrophages and analyzed the phagosomes by Western immunoblotting and mass spectrometry-based proteomics. Our purification procedure revealed that BCG grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 86 publications
5
92
2
Order By: Relevance
“…The results of studies on the phagolysosomal proteome vary depending on different factors: (i) the usage of cell lines or primary cells (23), (ii) the ingested particles e.g. latex beads, apoptotic cells, pathogen-associated structures or pathogens (16)(17)(18)22), (iii) the age of the phagolysosome (15,17), (iv) the analyzed fraction e.g. entire phagolysosome or membrane domains (detergent-resistant or detergent-soluble membranes) (15) and (v) the activation status of the cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies on the phagolysosomal proteome vary depending on different factors: (i) the usage of cell lines or primary cells (23), (ii) the ingested particles e.g. latex beads, apoptotic cells, pathogen-associated structures or pathogens (16)(17)(18)22), (iii) the age of the phagolysosome (15,17), (iv) the analyzed fraction e.g. entire phagolysosome or membrane domains (detergent-resistant or detergent-soluble membranes) (15) and (v) the activation status of the cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For several pathogenic microorganisms, proteomic studies unraveled the specific protein composition of phagolysosomes for a better understanding of the phagosomal maturation process and its modulation by pathogens (15)(16)(17)(18)(19)(20)(21)(22)(23). These studies demonstrated that the protein composition of the phagosome is highly dynamic, specific for the ingested particle, depends on the stage of phagosomal maturation, the type or cell line and the activation status of the phagocyte.…”
Section: Introductionmentioning
confidence: 99%
“…18 Jutras et al found that γ-secretase is a functional phagosome component that resides on newly formed phagosomes and remains associated with them throughout their maturation into phagolysosomes. 19 With proteomics, Nicastrin was found to be present on BCG-and latex-bead-containing phagosomes in human THP-1 macrophages 20 as well as on phagosomes from Mtb infected mouse bone-marrow-derived macrophages. 21 Nicastrin is a member of the γ-secretase that is an integral membrane-bound protease complex.…”
Section: Bacterial Phagosome Proteomics: the Bottleneck And The Promisementioning
confidence: 99%
“…Lee et al used radio-isotope labeled whole cell lysates that never saw latex bead or bacterial particles as an internal standard to estimate the degree of contamination from other organelles during a phagosome preparation. 20 The approach estimated the number of contaminating protein spots on a 2D gel but did not provide a quantitation of the contaminating fraction of individual proteins. However, it can be adapted for using stable-isotope labeling instead of radioactive labeling of host cells to estimate the contaminating fraction of of bacteria-mediated immunomodulation pathways.…”
Section: Phagosomes Are Self-sufficient Antigen Processing Organellesmentioning
confidence: 99%
“…Proteins involved in membrane trafficking and signal transduction such as Ras GTPase-activating-like protein IQGAP1 were detected to be regulated through a proteomic study [28]. In this study, the phagosomes from BCGinfected human macrophages were purified, and 447 human host proteins were identified.…”
Section: Host Proteins Regulated By Tbmentioning
confidence: 99%